Powers and Limits of the State During the COVID-19 Pandemic: A Critical Appraisal - Satriawan, Iwan; Seviyana, Devi (Universitas Airlangga, 2021)
The research aims to analyse the powers and limits of the State and whether Indonesia has properly adopted the concept of powers and limits during the state of emergency concerning the COVID-19 pandemic. The article adopted the normative legal research method, using the statute and case approaches for data analysis. The results show that a State may apply some types of power during an emergency. However, in using its powers, the government must consider the limits during a state of emergency. Indonesia has not properly adopted a balance of powers and limits during the state of emergency concerning the COVID-19 pandemic. While the government may take actions to respond to the pandemic, it cannot exceed the limitations on powers in accordance with the state of emergency principles. The State has tended to exceed the limits during the pandemic. In doing so, the State violated some state of emergency principles during the COVID-19 pandemic, such as temporariness, the rule of law, necessity, proportionally, intangibility, constitutionalism, harmony and supervision. The research recommends that in the future, the government and the House of Representatives (DPR) should obey the state of emergency principles, particularly in terms of State power limits to respect constitutional principles and the rule of law. In addition, individuals, groups of people or organisations may request judicial review of laws or regulations during a pandemic that violate the state of emergency principles to protect the fundamental rights of citizens.